Access 2013 - Balter, Alison; Safari eBooks ([S.l] : Que, 2013)
"Explore the most popular and some of the lesser known features of Access 2013 -Tables, Queries, Forms, Reports, Macros, and much more with Alison Balter as your guide! Start-to-finish personal training on Access 2013 : just watch and learn! Simple, quick video walkthroughs of the tasks you perform most often! Great personalized training at a fraction of the cost...for everyone who doesn't have time to read a book! These video lessons will ensure that you can harness the power of Access faster and more easily than ever before! In 13 thorough parts, Access 2013 LiveLessons shows you how to increase add finesse and polish to your presentations so they look like the pros. Expert Alison Balter simplifies powerful features and tools including Tables, Forms, reports, Queries, Macros, and much more! Truly harness the power built into Access! Just watch : You'll master high-powered skills at your own pace and get specific answers and solutions immediately, whenever you need them! For anyone who wants to master Microsoft Access 2013 fast!"--Resource description page.
Title from Title Screen (viewed Aug. 19, 2013).
Presenter, Alison Balter.
Keywords: Microsoft Access; Database management; Database design; Electronic books